Elephantine revisited: new insights into the Judean community and its neighbors - Folmer, Margaretha (Eisenbrauns, 2022)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Illustrations -- Preface -- List of Abbreviations -- Chapter 1. On the Archaeological Background of the Aramaic Papyri from Elephantine in the Light of Recent Fieldwork -- Chapter 2. Family Life and Law at Elephantine -- Chapter 3. Some Aspects of Family Bonds in the Judean Community of Elephantine -- Chapter 4. Law in Elephantine: Crimes and Misdemeanors -- Chapter 5. The Ostraca of Elephantine: A Further Light on the Judeans in Elephantine -- Chapter 6. Elephantine and Ezra-Nehemiah -- Chapter 7. Aḥiqar and Bisitun: The Literature of the Judeans at Elephantine -- Chapter 8. On Aḥiqar and the Bible -- Chapter 9. The Identity of the People at Elephantine -- Chapter 10. The Contribution of Elephantine Aramaic to Aramaic Studies -- Chapter 11. Personal Names in New Aramaic Ostraca from Syene -- List of Contributors -- Ancient Source Index -- Subject Index.